Incidence of graphic distortion in annual reports : a comparison study of Singapore and Hong Kong companies. - Iskandar Mirza. (2008)
The study looks into incidence of graphic usage and extent of graphic distortion between Singapore and Hong Kong annual reports. Paired samples analyzed against a scorecard showed that although relative differences in both incidence of graphic usage and distortion were insignificant, the level of distortion present in both were high.